0555 The Efficacy Of Nasal Airway Stent (nastent) On Obstructive Sleep Apnea And Prediction Of Treatment Outcomes. (27th April 2018) - Okuno, K; Minagi Ono, H; Ikai, K; Matsumura Ai, E; Takai, E; Fukatsu, H; Uchida, Y; Sakai, T
Abstract: Introduction: We performed a prospective study to evaluate the efficacy of nasal airway stent (Nastent) treatment, a nasopharyngeal stent that maintains the patency of the nasal airway to the nasopharynx and oropharynx during sleep, and examined predictors for Nastent treatment outcomes in patients with obstructive sleep apnea (OSA). Methods: Thirty patients were enrolled in this study. Cephalometric radiographs were obtained to analyze the craniofacial morphology at baseline. Before and after Nastent treatment, we evaluated OSA using a portable sleep study and Epworth Sleepiness Scale (ESS). Results: Twenty-nine subjects completed this study. There were significant decreases in the apnea hypopnea index (AHI) (22.4 ± 14.1 to 15.7 ± 10.4, p<0.01), CT<90% (2.3 ± 3.9 to 0.4 ± 0.7, p<0.05), and ESS (12.1 ± 4.3 to 6.7 ± 4.0, p<0.01), and a significant increase in the lowest SpO2 (81.9 ± 7.5 to 86.6 ± 4.8, p<0.01) by Nastent treatment. Subjects were divided into responders and non-responders based on reduction in AHI of >50% compared with baseline AHI. We evaluated the ratio of inferior airway space and middle airway space (IAS/MAS) on cephalograms as the index of the narrowest airway site. The IAS/MAS was significantly higher in responders than in non-responders (1.4 ± 0.9 vs. 0.9 ± 0.4, p<0.01) and predicted treatment responders with high accuracy (sensitivity: 90.9%, specificity: 88.9%, when IAS/MAS was set at 1.10). Conclusion: The Nastent device improved OSA, and cephalograms predicted treatment response with good sensitivity and specificity. Support (If Any):